Cognitive and physical functioning as predictors of everyday functioning: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Chan, Michelle L.; Eng, Chloe W.; Farias, Sarah Tomaszewski; Gilsanz, Paola; Whitmer, Rachel A.
Abstract: Background: Alzheimer's disease and associated cognitive impairments are major contributors to functional declines and difficulties with instrumental activities of daily living (IADL); however, it is postulated that functional decline is likely a product of multiple factors. Higher prevalence of cardiovascular conditions has been associated with greater vascular brain injury that can result in greater physical impairments (slower gait speed and reduced grip strength). Thus, physical functioning can also contribute to IADL disability. The current study examined how cognitive and physical functioning contribute to IADL functioning among a diverse ethnoracial sample. Method: The Kaiser Healthy Aging and Diverse Life Experience (KHANDLE) cohort is comprised of Kaiser Permanente Northern California members who are age ≥65, without a diagnosis of cognitive impairment or dementia, and who participated in Multiphasic Health Checkups between 1964‐1977. At enrollment, participants completed a self‐report measure of IADLs, neuropsychological testing measuring memory and executive functioning, and physical functioning assessment (grip strength and walk speed). Analyses include 1, 260 participants (401 Caucasian (32%), 339 African American (27%), 292 Asian (23%), and 228 Latino (18%)). Result: The sample was comprised of 59.05% females and average baseline age was 75.5 ± 6.8 years. When examined individually, executive functioning (p=0.0466), grip strength (p=0.0005), and walking speed (p<.0001) were significant predictors of IADL functioning after controlling for demographics (age, education, gender, self‐rated health). Memory (p=0.4468) was not a significant predictor. When considering all 4 of these predictors in a combined model, walk speed remained the only significant predictor of IADL performance (p<.000) with slower walking speed being associated with poorer IADL performance. This relationship also differed by race (p=0.0011), with slower walk speed having the greatest negative impact in Asians. Conclusion: There are limited studies examining how both cognitive and physical functioning predicts everyday functioning, particularly among a diverse ethnoracial sample. Our results indicate that among a cohort of older adults without a formal diagnosis of cognitive impairment or dementia, physical functioning, specifically walking speed, plays an important role in IADL difficulties. Importantly, when considering walking speed, executive functioning was no longer independently associated with IADL performance. Such findings have important implications in terms of screening older persons at risk for IADL disability.